The Supreme Being in Ciyawo Bible translation and managing the choice of adequate terms for God - Houston, T. J. (2022)
Planning for and managing a new Bible translation project is best undertaken when the context of the situation is well understood. This article uses Skopos theory and contextual frames as tools for understanding the Yawo contexts of Mozambique, Malawi, and Tanzania, as it relates to the choice of terms for God in Bible translation – particularly אֱלֹהִםי (ʾᵉlōhim) in the Hebrew Bible and θεός (theos) in the New Testament, but also applicable to other terms such as the personal name of Israel’s god, הוהי (yhwh). Skopos theory and narrative frame theory provide the theoretical basis of this article as African traditional religion and Islam are explored in the Yawo context. Special attention is paid to these narrative frames in application to translating adequate terms for the Supreme Being, or “God”, in Ciyawo Bible translation. This article shows that successful Bible translation in any context is possible when the relevant situation is understood and managed well.